Note:- 1) If y = cotx ; then dy/dx = -cosec^2(x)
2) If y = x^n ; where 'n' = constant ; then dy/dx = n*x^(n-1)
`y = x+cot(x)`
`dy/dx = y' = 1 - cosec^2(x)`
`or, dy/dx = -[cosec^2(x) - 1]`
`or, dy/dx = y' = -cot^2(x)`
Students, take our 5-minute (or less!) survey and you'll be entered to win a $50 Amazon gift card. Start Survey
We have a Math tutor online right now to help you!
To chat with a tutor, please set up a tutoring profile by creating an account and setting up a payment method. If you initiate a chat, please note you will be charged $0.50 a minute for tutoring time.